A Mini-Review on Detection Methods of Microcystins - Massey, Isaac Yaw (Toxins (Basel), 2020)
Cyanobacterial harmful algal blooms (CyanoHABs) produce microcystins (MCs) which are associated with animal and human hepatotoxicity. Over 270 variants of MC exist. MCs have been continually studied due of their toxic consequences. Monitoring water quality to assess the presence of MCs is of utmost importance although it is often difficult because CyanoHABs may generate multiple MC variants, and their low concentration in water. To effectively manage and control these toxins and prevent their health risks, sensitive, fast, and reliable methods capable of detecting MCs are required. This paper aims to review the three main analytical methods used to detect MCs ranging from biological (mouse bioassay), biochemical (protein phosphatase inhibition assay and enzyme linked immunosorbent assay), and chemical (high performance liquid chromatography, liquid chromatography-mass spectrometry, high performance capillary electrophoresis, and gas chromatography), as well as the newly emerging biosensor methods. In addition, the current state of these methods regarding their novel development and usage, as well as merits and limitations are presented. Finally, this paper also provides recommendations and future research directions towards method application and improvement.